Glocalization Of Education: A Study Of Ki Hajar Dewantara's Education Concept In A Glocal Perspective - Ermis Muhammad Qoiri Fahmi; Neni Mariana; Heru Subrata (LPPM Universitas PGRI Sumatera Barat, 2024)
Globalization brings the face of education in Indonesia so close to technological sophistication, progress in thinking and transformation in many aspects. However, the choice of globalization is not without risk, making educational institutions in Indonesia away from tradition and if not filtered, it will bring ideas that are contrary to the values of existing local wisdom. For this reason, Ki Hajar Dewantara's concept of education is offered as a solution to the distortions in the implementation of education in Indonesia. An in-depth study of Ki Hajar's thought can provide enlightenment in designing an education system that is able to answer global challenges while maintaining local wisdom, and one of the fruits of Ki Hajar's thought was the birth of Taman Siswa. Through Taman Siswa, Ki Hajar Dewantara devoted his energy and thoughts for the benefit of Nusa and the Nation. This research aims to examine the concept of glocalization of education in the context of Ki Hajar Dewantara's thought. This research uses a literature review method based on various literature sources, such as books, journals, articles, and official documents related to the concept of Ki Hajar Dewantara, the glocalization of education, and education in Indonesia. The results showed that the concept of global education includes the economic field, namely digitalization and the use of artificial intelligence, the socio-cultural field, namely western culture and also the tradition of thought from the west, and the academic field, namely the adoption of foreign curriculum, mastery of foreign languages, student exchanges, and so on. According to Ki Hajar, this global concept of education must be balanced with the concept of education based on local wisdom as an effort to maintain the identity and identity of the nation. Ki Hajar Dewantara's concept of education based on local wisdom includes 3 things, namely , local assets, Tradition, Values and beliefs.